The effect of synbiotic Streptococcus salivarius K12 and Musa acuminata on Candida albicans biofilm formation - Rismayuddin, Nurul Alia Risma; Mokhtar, Munirah; Othman, Noratikah; Ismail, Ahmad Faisal; Arzmi, Mohd Hafiz (Fakulti Perubatan dan Sains Kesihatan, 2019)
Introduction: Candida a/bicans is an opportunistic fungus that is associated with oral carcinogenesis. In addition, biofilm formation has been one of the important virulence factors of the yeast. Streptococcus salivarius Kl 2 is an oral probiotic while Musa acuminata is a well-known prebiotic. The objective of this study is to investigate the effect of 5. salivarius IK1 2 and M. acuminata skin aqueous extract (synbiotic) on C. albicans with the hypothesis that S. salivarius Kl 2 and M. acuminata inhibit C. a/bicansbiofilm formation. Methods: To develop mono-species biofilnn, C. a/bicans (A TCC MYA-4901 and cancer isolates, ALC2 and ALC3 strains) and 5. sa/ivarius Kl 2 were standardised to 1 OS cells and 106 cells, respectively and grown in 96-well plate iin nutrient broth (NB) or RPMI at 37 cc for 72 h. Polymicrobial biofilms were developed by inoculating both microorganisms in the same well with similar cell number as in mono-species. To determine the effect of synbiotic, similar protocol was repeated by mixing with 800 mg ml-1 of M. acuminata skin extract and incubated at 37 cc for 72 h. The medium was replenished at every 24 h, aseptically. Finally, the biofilms were assessed using crystal violet assay and the optical density was measured at 00620nm. Results: C albicans strain MYA-4901 and ALC3, when grown in polymicrobial with 5. salivarius Kl 2 in NB that is predominated by yeast-form C. albicans, exhibited decreased biofilms by 71.40± 11.7% and 49.40±3.9%, respectively when compared to the expected biofilms. Meanwhile in RPMI, which C. a/bicansstrain ATCC MYA-4901, ALC2 and ALC3 were predominated by hyphal-form showed decreased biofilms by 72.0±26.7%, 53.4± 14.4% and 65.7±6.7%, respectively when compared to the expected biofilms. Conclusion: 5. sa/ivarius Kl 2 and M. acuminata skin extract syn biotic inhibit biofilm formation of C. a/bicans yeast and hyphal forms thus supported tlhe hypothesis of the present study.